Pengaruh Kompetensi Aparatur Desa, Sistem Pengendalian Internal, Moralitas Individual, dan Locus Of Control Pada Pencegahan Fraud - I Gde Made Dhiyo Mahautama; Henny Triyana Hasibuan (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Prevention of fraud is really needed, especially in the management of village funds, so that the management and use of village funds can be in accordance with the direction and objectives of village development. The aim of this research is to empirically test the influence of village apparatus competence, internal control system, individual morality, and locus of control on preventing fraud in managing village funds. This research was conducted in 27 villages in Denpasar City, Bali with a sample of village officials using non-probability sampling, namely using a purposive sampling technique. The sample obtained in this study was 81 people. Data analysis uses multiple linear regression. The results of the analysis show that the competence of village officials has a positive effect on preventing fraud in managing village funds. The internal control system has a positive effect on preventing fraud in managing village funds. Individual morality has a positive effect on preventing fraud in managing village funds. Locus of control has a positive effect on preventing village fund management. The implication of this research is that by increasing the competence of village officials, implementing an adequate internal control system, the better individual morality implemented and supported by a good locus of control will be able to increase fraud prevention in managing village funds.